ANALYSIS OF HEAT TRANSFER CHARACTERISTICS OF TUBE BANKS ECONOMIZER USING NUMERICAL METHODS - Mohd. Qobar; Ahmad Syuhada; M. Ilham Maulana (Bulletin of Engineering Science, Technology and Industry, 2023)
The economizer is a heat exchanger that functions as a preheater for feed water in the boiler which is used to utilize flue gas which will improve the performance of the boiler by increasing the water temperature before entering the steam drum. The flue gas used comes from the furnace output which has a temperature of 1337oC, then the flue gas passes through the superheater with a temperature of 1070oC and enters the economizer with a temperature of 389oC. In order to maximize the use of the high temperature flue gas that enters the economizer, therefore in this scientific work we will analyze the heat transfer characteristics of the economizer in the MACCHI TITAN M package boiler at PT. PIM-2. This water tube type boiler has a capacity to produce steam of 120 tons/hour or 33. 3 kg/s with a pressure of 44 kg/cm2 and an economizer with a design surface dimension of 2345 m2, an in-line arrangement of tube banks, a tube diameter of 70 mm, a tube length of 1122 mm and a tube width of 2000 mm. Based on these data, an economizer will be analyzed by comparing the arrangement of tube banks and variations in the number of tubes (150, 200 and 250) in each tube bank using numerical simulation methods. From the simulation, it was found that the staggered tube banks with the 250 tube variation showed better heat transfer characteristics than the other variations, where the flue gas inlet temperature of 389 oC decreased to 257.7 oC and the increase in water temperature (H2O) from 110 oC increased to 193 oC or 75.45% of the inlet water temperature. tube length 1122 mm and tube width 2000 mm. Based on these data, an economizer will be analyzed by comparing the arrangement of tube banks and variations in the number of tubes (150, 200 and 250) in each tube bank using numerical simulation methods. From the simulation, it was found that the staggered tube banks with the 250 tube variation showed better heat transfer characteristics than the other variations, where the flue gas inlet temperature of 389 oC decreased to 257.7 oC and the increase in water temperature (H2O) from 110 oC increased to 193 oC or 75.45% of the inlet water temperature. tube length 1122 mm and tube width 2000 mm. Based on these data, an economizer will be analyzed by comparing the arrangement of tube banks and variations in the number of tubes (150, 200 and 250) in each tube bank using numerical simulation methods. From the simulation, it was found that the staggered tube banks with the 250 tube variation showed better heat transfer characteristics than the other variations, where the flue gas inlet temperature of 389 oC decreased to 257.7 oC and the increase in water temperature (H2O) from 110 oC increased to 193 oC or 75.45% of the inlet water temperature.